2007
DOI: 10.1007/s00330-007-0648-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparison between two MRI studies of the small bowel in Crohn’s disease, the oral contrast method and MR enteroclysis

Abstract: The aim was to compare bowel distension and diagnostic properties of magnetic resonance imaging of the small bowel with oral contrast (MRI per OS) with magnetic resonance enteroclysis (MRE). Forty patients with suspected Crohn's disease (CD) were examined with both MRI methods. MRI per OS was performed with a 6% mannitol solution and MRE with nasojejunal intubation and a polyethylenglycol solution. MRI protocol consisted of balanced fast field echo (B-FFE), T2 and T1 sequences with and without gadolinium. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(144 citation statements)
references
References 37 publications
0
134
0
10
Order By: Relevance
“…We, therefore, used a 3% mannitol solution in the expectation that mannitol's slight osmotic effect would produce better distention. This contrast agent is used at some institutions as part of a routine MR protocol for the examination of the small bowel, providing good small bowel distension without absorption [8,9,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, used a 3% mannitol solution in the expectation that mannitol's slight osmotic effect would produce better distention. This contrast agent is used at some institutions as part of a routine MR protocol for the examination of the small bowel, providing good small bowel distension without absorption [8,9,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Die Gefahr einer inkompletten Füllung ist bei der MR-Enterographie höher als beim MR-Enteroklysma [3,20]. Bei der Beurteilung von Patienten mit M. Crohn wurden jedoch keine signifikanten Unterschiede zwischen beiden Füllungsme-thoden gefunden, wenngleich oberfläch-liche Pathologien besser mit dem MREnteroklysma abgrenzbar waren [17,20,25] Befunde beim M. Crohn…”
Section: Mr-enterographieunclassified
“…While the question whether the contrast medium should be delivered to the intestinal tract orally (MR enterography) or via an already in place nasojejunal probe (MR enteroclysis) is widely debated, it has been the subject of only a few comparative studies. In their respective comparative studies, Masselli et al and Negaard et al found that significantly better distension was achieved with MR enteroclysis than with MR enterography [19,20]. However, Negaard et al were able to detect Crohn's-typical changes with high diagnostic accuracy and reproducibility using either method [20].…”
Section: Examination Prerequisites Protocol and Sequencesmentioning
confidence: 99%